P361MIP1 causes cardiomyopathy. (15th July 2014) - Buyandelger, B; Mansfield, C; Kostin, S; Choi, O; Isaacson, RL; Knoell, G; Mcsweeney, SJ; Lara-Pezzi, E; Milting, H; Knoell, R
Abstract: Purposes: Mutations in sarcomeric proteins are a major cause of hereditary cardiomyopathies. Muscle LIM protein (MLP, CSRP3) is involved in cardiac mechanosensation and important for myocyte-specific survival pathways. Identification of novel MLP interacting proteins (MIP) may provide novel insights into underlying molecular mechanisms of human disease. Methods and Results: Yeast two-hybrid screens identified MIP1 as a novel MLP interacting protein, which is a member of the poxvirus and zinc-finger (POZ or BTB) domain/zinc-finger transcription factor family. The interaction was confirmed by co-immunoprecipitation, cross-linking of recombinant proteins and immunohistochemistry. Cardiac myocyte specific conditional knockout mice (cKO) were generated and underwent transverse aortic constriction (TAC) to unveil potential gene effects. After 4 weeks of TAC left ventricles of cKO mice became dilated (LVIDd mm: 3.74 vs 3.44, LVIDs mm: 2.00 vs 1.65, cKO: n=10, Control: n=8, P<0.01) and exhibited impaired contractile performance (FS %: 46.46 vs 52.01, cKO: n=10, Control: n=8, P<0.05). Failing cKO hearts had significantly higher apoptotic events (8.5-fold, n=6 per group, P<0.001), increased activated caspase 3 (6.3-fold, n=6 per group, P<0.001) and marked replacement fibrosis. To understand the molecular mechanisms by which MIP1 regulates cardiac myocyte survival we applied apoptosis gene-focused PCR array analysis combined with genome wide chromatin immunoprecipitation-chip (ChIP-chip). As a result, the expression of pro-apoptotic genes was increased in cKO hearts subjected to TAC (Gene Set Enrichment Analysis, P<0.05). Hence MIP1 regulates a transcriptional program that protects cells against apoptosis. To examine further the effects of MIP1 on hypertrophy we overexpressed MIP1 in mouse heart (TG). MIP1 TG mice exhibited spontaneous cardiac hypertrophy with enlarged cardiac myocytes (n=150 cardiac myocytes per animal; n=5 mice per group, P<0.001) and increased Anf expression (n=3, P<0.05). Moreover ChIP-chip data showed binding of MIP1 to the calcineurin Aβ promoter, confirmed by ChIP-qPCR (P<0.05) and luciferase reporter assays (P<0.01). These data are supported by increased mRNA expression of calcineurin Aβ and Nfatc2 in TG (n=3, P<0.05) and decreased expression in cKO animals after TAC. MIP1 TG/calcineurin Aβ deficient mice did not develop cardiac myocyte hypertrophy which provides proof for the hypothesis that MIP1 interferes with the calcineurin pathway. Conclusion: MIP1 plays a major role in the protection of cardiac myocytes from apoptosis through modulation of both hypertrophic and cell death pathways.